FAKTOR PENYEBAB TINDAKAN KENAKALAN DI KALANGAN PENGGUNA PERPUSTAKAAN PERGURUAN TINGGI - Rahmi, Lailatur; Saputra, Agil; Nurhasanah (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2024)
Delinquent behavior in academic libraries poses a serious challenge to the optimization of libraries as centers of learning. Issues such as overdue book returns, mutilation of library materials, and vandalism of facilities are prevalent, causing significant disruption to library operations and other users. This study aims to identify the types of delinquent behaviors, their contributing factors, and potential solutions to mitigate these issues at the Academic Library X in Padang. Using a quantitative approach, the study surveyed 50 library users through structured questionnaires, with data analyzed descriptively. The findings reveal that 90% of respondents reported overdue book returns as the most common delinquent act, followed by concealing library materials (75%), mutilation of materials (60%), and vandalism of facilities (45%). The primary contributing factors include insufficient copies of library materials (85%), limited photocopying services (70%), high academic pressure (65%), and inadequate library security measures (60%). Proposed solutions include increasing the number of library material copies, improving photocopying services, strengthening security systems, and implementing user orientation programs for new students. Collaboration between the library and faculty is also recommended to enhance students' awareness of the importance of preserving library facilities and adhering to established rules. This study provides valuable insights for improving the sustainability of library services in academic environments.